PENGARUH SPESIALISASI INDUSTRI AUDITOR DAN AUDIT TENURE TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Selina Aulia Azahra; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2023)
This research aims to analyze and empirically test the effect between two dimensions of auditor quality, namely auditor industry specialization and audit tenure on audit report lag. The dependent variable used in this research is audit report lag. The independent variables are auditor industry specialization and audit tenure. The control variables are company size, leverage, profitability, and losses. The population of this research are banking companies listed on the Indonesia Stock Exchange in 2019-2021. The research sample consists of 115 financial reports from 41 banking companies. The data used in this research are secondary data and were selected using purposive sampling method. The data analysis technique using multiple linear regression methods. The results showed that the independent variable, namely auditor industry specialization, had a negative and significant effect on audit report lag, while audit tenure had no significant effect on audit report lag.